The English: English - Jakiatin Nisa; Wildan Insan Fauzi; Dedi Irwandi (Jurnal Sosioteknologi, 2023)
This research examines the application of brain-based learning (BBL) elements in social studies learning in Indonesia. It focused on social studies teachers in junior high schools in South Tangerang City and collected data from 100 social studies teachers. This research focused on social studies teachers in junior high schools in South Tangerang City. Each school is represented by one social studies teacher, so data is collected from 100 social studies teachers. The primary data collected in this study was obtained through the distribution of the questionnaire carried out via Google Form by utilizing the MGMP IPS in South Tangerang. The results show that the implementation of BBL in South Tangerang City did not run optimally because of two things: first, most of the BBL aspects had not been carried out optimally by teachers. Teachers rarely do many components of brain-based learning systems. Second, the survey results show that the five aspects of BBL are not carried out in harmony in social studies learning. BBL is a harmony learning pattern, where the five elements are carried out simultaneously, practically, and harmoniously because one part supports the other. If one part is too dominant, it will negatively impact learning outcomes.